2014
DOI: 10.3892/br.2014.298
|View full text |Cite
|
Sign up to set email alerts
|

Promoter region methylation and loss of protein expression of PTEN and significance in cervical cancer

Abstract: Abstract. The genetic basis underlying cervical tumorigenesis and progression are largely unknown. Phosphatase and tensin homologue (PTEN) is a tumor suppressor gene, and genetic changes of PTEN occurs in various types of cancer suggesting that the inactivation of PTEN may play an important role in the pathogenesis of a variety of human malignancies. In the present study, 102 cervical cancer specimens were examined for the expression of the PTEN gene and promoter methylation using methylation-specific-polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…In our estimate, the prevalence of PTEN methylation was 11.54% and 28.57% in patients' blood and tumor tissues, respectively. QI et al, (2014) showed that the frequency of PTEN promoter hypermethylation was 62% in tumor tissues of patients with cervical cancer where the methylation of the PTEN promoter was significantly related to the tumor grade, metastasis, and tumor stage (P<0.05). They found a significant association between the promoter methylation of PTEN and cervical cancer (P=0.042).…”
Section: Discussionmentioning
confidence: 99%
“…In our estimate, the prevalence of PTEN methylation was 11.54% and 28.57% in patients' blood and tumor tissues, respectively. QI et al, (2014) showed that the frequency of PTEN promoter hypermethylation was 62% in tumor tissues of patients with cervical cancer where the methylation of the PTEN promoter was significantly related to the tumor grade, metastasis, and tumor stage (P<0.05). They found a significant association between the promoter methylation of PTEN and cervical cancer (P=0.042).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous heterozygotes are deleted in cervical cancer tissues, which are located in D10S198 and D10S192 sites (31). It has been suggested that inactivation of the PTEN gene and inhibition of protein expression may promote the progression of cervical cancer (32,33). However, the PI3K/AKT signaling pathway is abnormally activated in cervical cancer tissues (34).…”
Section: Discussionmentioning
confidence: 99%
“…In cervical cancer, PTEN variants were shown to be associated with HPV-negative adenocarcinoma [75], although it was not reproduced in other studies [76]. The epigenetic regulation of gene expression seems to be relevant for PTEN as it is hypermethylated in cervical cancer and associated with the disease stage [77] and histological type [78], which is consistent with lower levels of PTEN and PTEN silencing [76,79]. The methylation events were also reported to be affected by the SNV in the CpG islands c.-9C > G, which modifies the methylation status and thus gene expression [80].…”
Section: Cell Cycle Regulation and Dna Repairmentioning
confidence: 93%